Dismantling Russia's Northern Fleet Nuclear Submarines: Environmental and Proliferation Risks - Snell, Benjamin A. (2000)
This thesis examines the 1986 Chernobyl accident and its consequences as the basis for an analysis of the possible dimensions of the nuclear catastrophes that could occur during the dismantlement process of Russia's Northern Fleet nuclear submarines. It assesses the potential demographic, ecological, and economic consequences of a nuclear accident. Given the systemic problems at Russian nuclear facilities, the risks of a catastrophic event in the poorly maintained and operated submarine yards housing over 100 operating nuclear reactors are significant. A major nuclear accident at these facilities could cause damage to the environment of global proportions. This thesis considers the potential environmental impact of a nuclear accident during the nuclear submarine dismantlement process and discusses the environmental damage that has already occurred as a result of Soviet and Russian practices. This thesis also evaluates the risk of diversion of nuclear materials to proliferators or terrorists. Lastly, this thesis examines how the United States, the European Union, and perhaps others could assist Russia in reducing the environmental and proliferation risks in this dismantlement process.